Psicologia escolar e juventudes: entre caminhos e armadilhas - Costa, Maraiza Oliveira (2016)
This dissertation is part of the Research Line "Historical Foundations of Psychology" of the Post-Graduate Program in Psychology at the Federal University of Goiás. The aim of the study was to analyze in which ways the conceptions of young people on youth and on School Psychology can contribute to problematize the psychologist's practice at school. In order to achieve that goal, the theoretical framework conceptualized interfaces between Psychology and Education, as well as the theoretical debates on the youth and teenage conceptions. The theoretical fundamentals: (1) positions itself in favor of a critical conception of School Psychology, which appropriates the contributions of Marxism and the Historical-Critical Pedagogy; (2) defends the use of the term youths in order to emphasize the historical-social nature of the human development process. In addition, an empirical qualitative research was carried out in which were proposed semistructured interviews with four young individuals who attended the Integrated School to Technical at the Federal Institute of Education, Science and Goiás Technology. The content analysis indicated the existence of gaps between a proposal of a critical School Psychology Review and the conception of young people about psychology as a profession: it is seen markedly as clinical-traditional and characterized by a focused action at the student-problem. Moreover, the adolescence and youth conceptions carry many contradictions. While the former is strongly associated with pathologizing and negative conceptions, the second expresses certain types of experiences, such as the transition to adulthood and the emergence of new responsibilities. The empirical study and theoretical discussions developed in this work indicate as key challenges for the construction of praxis in School Psychology: the compression of the historical-social nature of youths and adolescences, and the need to overcome the clinical and individualistic model of the psychologist in school performance.